2018
DOI: 10.1002/ijc.31786
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights of epithelial protein lost in neoplasm in prostate cancer metastasis

Abstract: EPLIN is frequently downregulated or lost in various cancers. The purpose of this study was to evaluate the importance of EPLIN in prostate cancer progression, with particular focus on the mechanistic implications to elucidate EPLIN's tumor suppressive function in cancer. EPLIN expression was evaluated in prostate cancer cell lines and tissues. PC-3 and LNCaP EPLINα overexpression models were generated through transfection with EPLINα sequence and EPLIN knockdown was achieved using shRNA in CA-HPV-10 cells. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 42 publications
(117 reference statements)
2
20
0
Order By: Relevance
“…On the other hand, EPLIN loss of expression has been associated with cancer. This has been shown to affect cancer cell adhesion and migration and increase metastatic potential (Collins et al, 2018;Jiang et al, 2008;Liu et al, 2012;Sanders et al, 2010;Zhang et al, 2011). Like LUZP1, EPLIN had never been implicated in cilia biology.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, EPLIN loss of expression has been associated with cancer. This has been shown to affect cancer cell adhesion and migration and increase metastatic potential (Collins et al, 2018;Jiang et al, 2008;Liu et al, 2012;Sanders et al, 2010;Zhang et al, 2011). Like LUZP1, EPLIN had never been implicated in cilia biology.…”
Section: Introductionmentioning
confidence: 99%
“…EPLIN is widely expressed in normal epithelial cells but frequently lost in cancer cells and tissues [6][7][8]18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, EPLIN engages in cell-cell adherence junctions by linking the cadherin-β-catenin-α-catenin-EPLIN-F-actin complex. It is also suggested to interact with paxillin [11,[16][17][18] and plays an indispensable role in stabilising apical-basal polarity in epithelial cells [9]. Previous studies revealed that EPLIN negatively correlates with epithelial mesenchymal transition (EMT), invasiveness, metastasis, poor prognosis, mortality and therapeutic resistance in human tumours such as prostate, breast, ovarian and oesophageal cancers [6,7,9,19,20], and that epidermal growth factor (EGF) could cause protein phosphorylation and turnover of EPLIN through an extracellular signal-regulated kinase (ERK) signal pathway to influence EMT [21].…”
Section: Introductionmentioning
confidence: 99%
“…Invasive ability in vitro is important in determining tumor metastasis potential [30]. Wound-healing assay and Transwell chamber analysis data showed that the metastasis ability of ovarian cancer SKOV3 cells was significantly decreased after transfection of the ELF5 gene, indicating that the ELF5 gene has a significant inhibitory effect on host invasion and motility of ovarian cancer SKOV3 cells.…”
Section: Discussionmentioning
confidence: 99%